Synthesis and characterization of quaternary La(Sr)S–TaS2 misfit-layered nanotubes - Serra, Marco; Anumol, Erumpukuthickal Ashokkumar; Stolovas, Dalit; Pinkas, Iddo; Joselevich, Ernesto; Tenne, Reshef; Enyashin, Andrey; Deepak, Francis Leonard (Beilstein Journal of Nanotechnology, 2019)
Misfit-layered compounds (MLCs) are formed by the combination of different lattices and exhibit intriguing structural and morphological characteristics. MLC SrxLa1−xS–TaS2 nanotubes with varying Sr composition (10, 20, 40, and 60 Sr atom %, corresponding to x = 0.1, 0.2, 0.4 and 0.6, respectively) were prepared in the present study and systematically investigated using a combination of high-resolution electron microscopy and spectroscopy. These studies enable detailed insight into the structural aspects of these phases to be gained at the atomic scale. The addition of Sr had a significant impact on the formation of the nanotubes with higher Sr content, leading to a decrease in the yield of the nanotubes. This trend can be attributed to the reduced charge transfer between the rare earth/S unit (LaxSr1−xS) and the TaS2 layer in the MLC which destabilizes the MLC lattice. The influence of varying the Sr content in the nanotubes was systematically studied using Raman spectroscopy. Density functional theory calculations were carried out to support the experimental observations.
Keywords: aberration-corrected STEM; DFT; misfit-layered compounds; nanotubes; Raman spectroscopy